Write in tune contemporary music in fiction - Hertz, Erich; Roessner, Jeffrey (Bloomsbury, 2015)
"Focusing on Anglo-American novels of the past two decades, Write in Tune explores the dynamic intersection between popular music and fiction"--Provided by publisher.